Enhancing Institutional Performance Through Educational Quality Management Based on the Plan do Check Act (PDCA) Cycle - Muhammad Akhir; Zainidah Siagian; Rustam Ependi; Rahmat Rifai Lubis (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2026)
This study examines the implementation of Plan–Do–Check–Act (PDCA)-based educational quality management in improving institutional performance at MAS Al Ittihadiyah Bromo Medan. The study employed a qualitative case study design involving the principal, vice principals, teachers, administrative staff, school committee members, and relevant institutional documents. Data were collected through observations, semi-structured interviews, and document analysis, and analyzed using data reduction, data display, and conclusion drawing, while credibility was ensured through source and technique triangulation. The findings reveal that institutional performance improvement is supported by the systematic implementation of the PDCA cycle across strategic planning, program implementation, monitoring, evaluation, and continuous improvement. The planning stage demonstrates increasing stakeholder participation and strategic orientation, while implementation reflects collaborative governance and quality-focused educational services. However, evidence-based planning, standardized performance indicators, documentation systems, digital infrastructure, and follow-up mechanisms require further strengthening to optimize institutional effectiveness. The study concludes that PDCA functions as an effective quality management framework for fostering continuous organizational improvement, strengthening accountability, promoting data-driven decision-making, and enhancing the institutional performance and educational quality of Islamic senior high schools.